Phép kéo theo trên dàn con X2 của dàn phân phối RHA - Hòa, Đào Thu (Journal of Computer Science and Cybernetics, 2016)
Implication operators on lattices play  a considerable role in  studying reasoning methods and  hence they have been examined extensively by many authors (see [4]). It is shown in [5] that refined hedge algebras  are an algebras foundation to investigate linguistic-valued logic and  reasoning methods. So,  the main aim of the paper is to examine implication operators in a restricted class of refined hedge algebras and to establish some formulas to compute these operators.